Dissemination of routing information in broadcast networks OSPF versus IS-IS. - Sharon, O.
OSPF and IS-IS are two main standard link state routing protocols designed to operate in various complex network topologies. One aspect that both protocols handle is the reliable dissemination of routing information over broadcast networks such as Ethernet and FDDI. Both protocols suggest different schemes for this purpose and in this article we compare the two. The performance criteria being checked are: the longest arrival time of a routing update packet at all the routers; the average arrival time of routing update packets at all the routers; the total required bandwidth; and the number of memory accesses a router performs, which is evidence of the amount of internal work it performs. We find that in our model of broadcast networks the scheme suggested in IS-IS is more efficient than that of OSPF in terms of the arrival times of routing update packets. In particular, the average arrival time of routing update packets in OSPF is 2-10 times longer than in IS-IS. In terms of the bandwidth each scheme consumes, there are scenarios where OSPF outperforms IS-IS and vice versa. In terms of the number of memory accesses routers perform in each scheme, IS-IS outperforms OSPF
Keywords: Ethernet; FDDI; IETF; IS-IS.; ISO; International Organization for Standardization; Internet Engineering Task Force; OSPF; Average arrival time; Broadcast networks; Intermediate system to intermediate system; Internal work; Longest arrival time; Memory accesses; Network topologies; Open shortest path first; Performance criteria; Routing information dissemination; Routing update packet; Routing update packets; Standard link state routing protocols; Total required bandwidth